-4(-2x+2)+8x=-(5x+7)

Simple and best practice solution for -4(-2x+2)+8x=-(5x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-2x+2)+8x=-(5x+7) equation:


Simplifying
-4(-2x + 2) + 8x = -1(5x + 7)

Reorder the terms:
-4(2 + -2x) + 8x = -1(5x + 7)
(2 * -4 + -2x * -4) + 8x = -1(5x + 7)
(-8 + 8x) + 8x = -1(5x + 7)

Combine like terms: 8x + 8x = 16x
-8 + 16x = -1(5x + 7)

Reorder the terms:
-8 + 16x = -1(7 + 5x)
-8 + 16x = (7 * -1 + 5x * -1)
-8 + 16x = (-7 + -5x)

Solving
-8 + 16x = -7 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-8 + 16x + 5x = -7 + -5x + 5x

Combine like terms: 16x + 5x = 21x
-8 + 21x = -7 + -5x + 5x

Combine like terms: -5x + 5x = 0
-8 + 21x = -7 + 0
-8 + 21x = -7

Add '8' to each side of the equation.
-8 + 8 + 21x = -7 + 8

Combine like terms: -8 + 8 = 0
0 + 21x = -7 + 8
21x = -7 + 8

Combine like terms: -7 + 8 = 1
21x = 1

Divide each side by '21'.
x = 0.04761904762

Simplifying
x = 0.04761904762

See similar equations:

| X-47=12 | | X+3=3+2(2+3x)-5x | | x+x-30=180 | | 6(6x-11)=54x | | b=60+(15+7) | | -5d=20 | | x-30=180 | | (8x-4)+(10x+6)= | | 5x-3=-3x-1 | | (X-7)+12=20 | | 7a-18=-3(-3+3)+7a | | x+15=4x-36 | | -40=b-51 | | H=7+27t-16t^2 | | x*15=4x-36 | | 6(x-11)=54x | | -9r-18r-3r=-12 | | 28=4s+r-s | | 4(3x+3)=3(5x+0.5) | | 1204.2528=2*3.14*6.8*6.8+2*3.14*6.8*h | | 4a-3a=a | | 0=x^2+2x+420 | | 4p+2=-3p+5p | | 4x+0.5= | | h=-2t^2+8t | | h=-2t^2+8tZ | | 17.18=3g+3.89 | | 11-3a=1-a | | lnx+ln(x-2)=0 | | (2x+5)*(3x+2)=0 | | 2*3.14=65.9 | | x-20=-69 |

Equations solver categories